Lithological and micropaleontological characteristic of the Stella Creek bottom sediments (Antarctic Peninsula western shelf) - O. P. Olshtynska; S. B. Shekhunova; S. M. Stadnichenko; O. S. Ogienko; V. V. Permyakov (Ukrainian Antarctic Journal, 2019)
Main objective of the study – comprehensive research of material, particle size, mineral, chemical and micropaleontological composition, together with analysis of depositional environment of the Stella Creek bottom sediments. Material – bottom sediments samples of the Stella Creek, a small inter-island section, which is the terminal drainage basin of the Galindez and Winter islands from the water area adjacent to the Ukrainian Antarctic Akademik Vernadsky station were studied. Methods: particle size, mineral and chemical composition analyses were carried out using a scanning electron microscope with microprobe analysis; ultrasonic disintegration of rocks was used to remove paleontological remains; photographing and determining the taxonomic composition of microalgae were performed with light and electron microscopes. Results. The mineral composition of the bottom sediments is represented by quartz, plagioclase, chlorite (iron-containing clinochlore), illite, opal (biogenic), amphibole (hornblende), siderite. Among terrigenous minerals of heavy fraction, ilmenite (with manganese), zircon, and monazite are determined. Authigenic minerals are represented by bacteriomorphic framboidal clusters of iron sulfide microcrystals, calcium sulfate, and barite. Among the organic residues in sediments, diatom frustules predominate. Diatoms have three intervals, which coincide with the layers defined by particles size distribution analysis. Conclusions. Bottom sediments were formed in Late Quaternary time in cold-sea conditions and low hydrodynamic activity with local conditions favorable for early diagenetic biogenic sulfate reduction.